REVIEW OF SECURITY ATTACKS ON SOFTWARE DEFINED NETWORKING (Pakistan Journal of Scientific Research, 2023)
Now a days use of software defined networking increases in industry and in different enterprises due to its capabilities like centralized architecture, Data plan and control plan separation, different available controllers in different languages, very helpful in monitoring the network flow and other type of working behavior and security measures can be taken in SDN. In this article we will provide a brief overview of SDN and then we try to elaborate each and every thing to do our best like related existing work, architecture of SDN its security threats and also try to describe the SDN security attacks defense mechanism existing work with references that will be very helpful for readers to understand an SDN attacks and solutions. In short SDN becoming popular in future and also being used for many security measures to solve the security issues because SDN is also a technique that can be used as a part of security solution that is a very helpful in future. We also give a future direction at the end that is a really a novel research problem and must be solved to secure the SDN network.
Keywords: Software defined networking; control plan; data plan; SDN security